Whole genome comparative analysis of channel catfish (Ictalurus punctatus) with four model fish species - Jiang, Yanliang (BioMed Central, 2013)
BACKGROUND: Comparative mapping is a powerful tool to study evolution of genomes. It allows transfer of genome information from the well-studied model species to non-model species. Catfish is an economically important aquaculture species in United States. A large amount of genome resources have been developed from catfish including genetic linkage maps, physical maps, BAC end sequences (BES), integrated linkage and physical maps using BES-derived markers, physical map contig-specific sequences, and draft genome sequences. Application of such genome resources should allow comparative analysis at the genome scale with several other model fish species. RESULTS: In this study, we conducted whole genome comparative analysis between channel catfish and four model fish species with fully sequenced genomes, zebrafish, medaka, stickleback and Tetraodon. A total of 517 Mb draft genome sequences of catfish were anchored to its genetic linkage map, which accounted for 62% of the total draft genome sequences. Based on the location of homologous genes, homologous chromosomes were determined among catfish and the four model fish species. A large number of conserved syntenic blocks were identified. Analysis of the syntenic relationships between catfish and the four model fishes supported that the catfish genome is most similar to the genome of zebrafish. CONCLUSION: The organization of the catfish genome is similar to that of the four teleost species, zebrafish, medaka, stickleback, and Tetraodon such that homologous chromosomes can be identified. Within each chromosome, extended syntenic blocks were evident, but the conserved syntenies at the chromosome level involve extensive inter-chromosomal and intra-chromosomal rearrangements. This whole genome comparative map should facilitate the whole genome assembly and annotation in catfish, and will be useful for genomic studies of various other fish species.